Functional outcomes and patient satisfaction after fasciotomy performed for chronic exertional compartment syndrome - Marais, Christoff de Villiers (Department of Health and Rehabilitation Sciences, 2017)
Study Rationale: Chronic exertional compartment syndrome often forces patients to change their sporting activities or reduce their level of participation. Many undergo surgery with the aim to return to their activities symptom free. The aim of the study was to determine if fasciotomies for chronic exertional compartment syndrome are a reliable treatment option with a predictable outcome to allow patients to return to the same level of activities. Objective: The evaluation of the functional outcomes and patient satisfaction in an active population who had surgery, namely fasciotomies, for chronic exertional compartment syndrome (CECS) of the lower leg. Design: A retrospective descriptive cohort study with a telephonic follow-up interview. Patients: A consecutive series of 41 patients that were surgically treated for CECS by a single orthopaedic surgeon from July 2005 to October 2013. Main Outcome Measures: Patient records were reviewed to determine their presenting symptoms, diagnostic investigations and surgical procedures performed. A questionnaire was completed by each participant to assess pain and level of activity before and after surgery, level of improvement after surgery and patient satisfaction with surgical outcomes. Results: Twenty-one of the 41 patients that were included in the study were categorized as active sportsmen, participating at a competitive or a non-competitive level. The remaining 20 were experiencing symptoms during leisure activities. The majority of all the patients (63%) had to stop their activity due to their symptoms. After surgery 95% were able to return to participate in the same level of activities as before surgery. Ninety percent of the active sportsmen were able to return to participation at a competitive or non-competitive level, with 45% reporting an increase in the level of intensity that they could maintain. Overall satisfaction was reported by 80% of participants although only 46% were completely pain free. Conclusions: Fasciotomies are a viable surgical treatment option for chronic exertional compartment syndrome in active patients, including athletes. There is an 87% return rate to previous activities within 6 months and an 80% satisfaction rate reported by patients post-surgery. We do acknowledge that some of the data collected regarding symptomology is subject to recall bias due to the interval between surgery and completion of the questionnaire.